## SHOW YOUR SOLUTION set is a driver providing a professional motorcycle ride to commuters he has a base care of php 50 for the first 2 k

Question

set is a driver providing a professional motorcycle ride to commuters he has a base care of php 50 for the first 2 km travelled php 10 for every kilometer thereafter.
Questions:
1.write the line equation expressing the fare paid (y) in relation of the distance (x) covered by a motorcycle.
2.How much will seth receive if they travel 5 km?
3.About how many kilometers can a passenger travel if he she has php 120?
4.using your answer in number one will write the equation of the line in the form Ax + By = C.

in progress 0
3 years 2021-07-28T06:01:06+00:00 1 Answers 73 views 0

1. We are given:

The base care + first 2 km price = 50 php

Cost for every subsequent km = 10 php

Solving the questions:

Question 1:

We are given that the driver will charge 50 php for the first 2 km

and then will charge 10 php for every km after that

In the equation, (y) has to be the fare paid and (x) is the distance travelled

So, our fare (y) will be 50 php the second we sit on the bike, and after the first 2 km, we will be charged 10php/km

It can be written as:

y = 50 + 10(x-2)

I multiplied 10 by x-2 since the price of 10 php/km starts after we have travelled 2 km

Question 2:

Since we now have our equation, we are asked the cost if We travel 5 km

y = 50 + 10(x-2)

We know that in this equation, x is the distance travelled and y is the fare

Since we are told that the distance covered is 5 km:

y = 50 + 10(5-2)

y = 50 + 30

y = 80 php

Question 3:

We are asked the distance travelled if we have 120 php

We know that in the equation, y is the fare paid and x is the distance travelled

Since we are told that the fare paid is 120 php:

y = 50 + 10(x-2)

120 = 50 + 10(x-2)

120 – 50 = 10x – 20

10x = 90

x = 9 km

Question 4:

Rewriting our equation in the form, Ax + By = C

We have the equation:

y = 50 + 10(x-2)

y = 50 + 10x – 20

y = 30 + 10x

0 = 30 + 10x – y                                  [subtracting y from both sides]

10x – y = -30                                      [subtracting 30 from both sides]